The science and praxis of complexity : contributions to the symposium held at Montpellier, France, 9-11 may, 1984. - Shūhei, Aida; P. M., Allen; H., Atlan; Boulding, K. E.; Chapman, G. P.; Costa de Beauregard, O.; Danzin, A.; Dupuy, J.-P.; Giarini, O.; Hägerstrand, T.; Holling, C.S.; J. L.,Kirby M.; et al. (Japan : The United Nations University, 1985)
"The symposium represented the first venture of the United Nations University into this new domain of scientific endeavour concerned with the nature and behaviour of complex dynamic systems and the phenomenon of complexity. It was designed to provide a mapping of the states of-the-art, of recent findings and approaches as they have emerged in different disciplines and areas of research." (Copied of the preface).
Preface. Opening statement. Introduction. 1. Understanding complexity. 2. Complexity in focus. 3. Complexity in nature. 4. Complexity in society. 5. Overview. Participants.
Contains bibliographical references in each chapter
Keywords: SCIENCE; CLOSED ECOSYSTEMS; INFORMATION THEORY; COMPLEXITY -- PHILOSOPHY; DECISION -- MAKING; CONFERENCE PAPERS AND PROCEEDING